PENGARUH KONSENTRASI MALTODEKSTRIN DAN SUHU PENGERINGAN TERHADAP KARAKTERISTIK BUBUK MINUMAN SINOM - Indri Paramita, I.A.Made; Mulyani, Sri; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
ABSTRACT The aims of this study were to 1) determine the effect of the concentration of maltodextrin and drying temperature on the characteristics of the powder drinks sinom and 2) determine the concentration of maltodextrin and drying temperature on the production of powder beverage sinom with the best characteristics. This study used a there are two experiments that attempt to see the effect of drying temperature and maltodextrin concentration. The experimental design used was a split plot design (split plot design) with two treatment factors. The main plot is the drying temperature is used which consists of 3 levels ie 45oC, 50oC and 55oC. The concentration of maltodextrin as a subplot consisted of three levels, namely 15%, 20% and 25%. In this experiment there are 9 combinations for each of groups as musch as to 2 obtain, so there are 18 experimental units. The parameters research water content, solubility and sensory testing The results showed the concentration of maltodextrin and drying temperature as well as the interaction treatment significantly affected the water content, respectively the yield and the solubility of treatment and no significant interaction Concentration maltodextrin 25% and drying temperature of 45oC produces the best characteristics of powder sinom beverages with: the water content 9.31%, yield 40,90%, 99.28% solubility, and sensory testing 4.95 color (yellow), aroma 3.45 (typical sinom beverages) and the overall acceptance of 3,70 (liked). Keywords: maltodextrin, drying temperature, antioxidants and sinom.
Keywords: 43